2019
DOI: 10.1002/ejp.1366
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine infusion for 96 hr after thoracotomy: Effects on acute and persistent pain

Abstract: Introduction Pain which persists after thoracotomy is well recognized, and activation of the N‐methyl‐d‐aspartate (NMDA) receptor could be a contributing factor. This study sought to establish whether ketamine given peri‐operatively could reduce persistent post‐surgical pain. Trial design Double‐blind, randomized, placebo‐controlled trial comparing low‐dose intravenous ketamine and saline placebo. Methods Seventy patients undergoing thoracotomy were randomized to receive either intravenous ketamine (0.1 mg kg−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 21 publications
1
65
0
Order By: Relevance
“…Several studies have investigated the efficacy of intravenous ketamine on acute postoperative thoracotomy pain (12,19,(21)(22)(23)(24)(25). There is no consensus in standard dose, timing and route of administration of ketamine among studies (12).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the efficacy of intravenous ketamine on acute postoperative thoracotomy pain (12,19,(21)(22)(23)(24)(25). There is no consensus in standard dose, timing and route of administration of ketamine among studies (12).…”
Section: Discussionmentioning
confidence: 99%
“… 28 Similarly, a randomized controlled trial conducted by Chumbley et al showed that ketamine did not cause a reduction in opioid use six and 12 months after thoracic surgery. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Comparing the reported user rates at 3 and 12 months after surgery, shows a decrease in every area. In 5 of 7 scenarios (6 studies), that give information about use during the follow up year, the absolute reduction of opioid users was smaller than 10 percentage points (Simoni et al 10 : -5.6%; Dengler et al ( 8): -2 %; Blågestad et al 16 : -0.6 %; Fenten et al 14 : FNB -2.5%; Chumbley et al 12 : -8.19 %). Just Grosu et al 18 and Fenten et al 14 (LIA group) reported a higher reduction of user rated from the third to the twelfth month after surgery (Grosu et al 18 : -20%; Fenten et al 14 : LIA -10.6%).…”
Section: Evolution 3 To 12 Months After Surgerymentioning
confidence: 99%
“…2019) analysed 70 thoracotomy patients in the UK, that were not using strong opioids preoperatively. 12 The patients were randomised to receive either intravenous ketamine or saline placebo for 96 hours, starting 10 minutes prior surgery. 34 patients were randomised in the "saline placebo" group and were relevant for us.…”
Section: Other Operation Typesmentioning
confidence: 99%